2007
DOI: 10.1007/s10295-007-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of low rank coal by Trichoderma atroviride ES11

Abstract: A new isolate of Trichoderma atroviride has been shown to grow on low rank coal as the sole carbon source. T. atroviride ES11 degrades approximately 82% of particulate coal (10 g l(-1)) over a period of 21 days with 50% reduction in 6 days. Glucose (5 g l(-1)) as a supplemented carbon source enhanced the coal solubilisation efficiency of T. atroviride ES11, while 10 and 20 g l(-1) glucose decrease coal solubilisation efficiency. Addition of nitrogen [1 g l(-1) (NH(4))(2)SO(4)] to the medium also increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Evx1. Previous studies have shown that certain Trichoderma strains are able to solubilize and even degrade sub-bituminous coal compounds (Silva-Stenico et al, 2007). Moreover, it is worth noting that, when grown on YMA Petri dishes added with dibenzothiophene (DBT) crystals, the fungal strain Evx1 caused the medium to become golden yellow, a reaction ascribable to the formation of 3-hydroxy-2-formylbenzothiophene (HFBT) an intermediate in the DBT degradation pathway (Bressler and Fedorak, 2001).…”
Section: Thicoderma Sp As a Biocatalystmentioning
confidence: 99%
“…Evx1. Previous studies have shown that certain Trichoderma strains are able to solubilize and even degrade sub-bituminous coal compounds (Silva-Stenico et al, 2007). Moreover, it is worth noting that, when grown on YMA Petri dishes added with dibenzothiophene (DBT) crystals, the fungal strain Evx1 caused the medium to become golden yellow, a reaction ascribable to the formation of 3-hydroxy-2-formylbenzothiophene (HFBT) an intermediate in the DBT degradation pathway (Bressler and Fedorak, 2001).…”
Section: Thicoderma Sp As a Biocatalystmentioning
confidence: 99%
“…Chief amongst these enzymes is LiP, MnP, and the phenol oxidase, LAC. [23][24][25][26][27][28][29] Preliminary screening by the culturing of strain ECCN 84 on PDA plates in the presence and absence of substrates for MnP (MnCl 2 ) and LAC (ABTS) indicated a positive response for LAC activity only (data not shown). Consequently, experiments were carried out to confirm the presence of extracellular LAC activity in culture filtrates of ECCN 84 and to determine whether this strain responded to the addition of waste coal by increasing activity of LAC and the results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas oleovorans grew faster in the addition of available nitrogen sources (Füchtenbusch and Steinbüchel 1999). Silva-Stenico et al (2007) reported that addition of a nitrogen source such as (NH 4 ) 2 SO 4 to the medium also increased the coal solubilization efficiency of T. atroviride ES11. …”
Section: Effect Of Carbon Source On Biodepolymerization Of Coalsmentioning
confidence: 99%
“…A new isolate of T. atroviride has been shown to grow on low rank coal as the sole carbon source. T. atroviride ES11 degraded 82% of particulate coal over a period of 21 days with 50% reduction in 6 days (Silva-Stenico et al 2007). Only limited information is available regarding the molecular mechanisms of coal biosolubilization by fungi (Fakoussa 1981).…”
Section: Introductionmentioning
confidence: 99%